VLAN Wireless Performance Analysis Of Central Access Point Management Topology According to the IEEE 802.11 Standard - Arief Ikhwan Wicaksono; Chanief Budi Setiawan (Compiler, 2019)
Wireless network distribution is the right solution to disseminate network services in places and areas that are difficult to reach by cable networks. The effort to add a number of access points is intended to increase the coverage area of a network service so that the signal coverage can be even and broad. The development and improvement of wireless network users have made management and user management activities not easy, because of the way wireless technology works in the operational delivery of its packages, sorting and dividing the packages into 3 parts. Among them are packaged in the form of management, control, and data. Whereas if the management prioritizes data without considering management and control, the emergence of vulnerability in network distribution activities will occur when users are increasingly populated. To facilitate the flexibility and mobility of centralized wireless network users, this study utilizes VLANs that will be implemented at OSI Layer 2 to facilitate the classification of user-profiles, subnetting, securing, and roaming features between access point devices and their users. This research in its testing uses QoS parameters that refer to ITU G.165 / G.168 to monitor the quality of services provided. The parameters used in the measurement of interconnection include Throughput, Packet Loss Ratio, Latency, Jitter, and Delay. If the test is declared successful and complete, it is continued by analyzing and evaluating the results of the study in the hope that the system will successfully cluster the users based on the user characteristic dataset